Influence of animal temperament on body and reproductive development of beef bulls - da Silva, Mariana Karla Francolino (2025)
Several studies have related reactive temperament to poorer productive and reproductive performance in cattle. However, no studies have aimed to investigate the effect of temperament on sexual development and precocity of male cattle. The objective of this study was to test the hypothesis that reactive animals exhibit delayed sexual development and poorer reproductive performance. For the study, 40 crossbred male cattle (Nellore x Santa Gertrudis) at 12 months were selected. The animals underwent behavioral evaluation and were divided into two groups: calm (CA; n = 24) and reactive (RE; n = 16). All steers were weighed to monitor weight gain, and blood samples were collected to measure cortisol and testosterone concentrations. Semen collections by electroejaculation were performed to determine the onset of puberty and assess sperm quality. Cryopreservation tests were conducted, and the samples were evaluated for kinetics and plasma membrane integrity. Ultrasound examinations assessed testicular development. Additionally, testicular biopsies were performed to evaluate spermatid and spermatozoa ratios. There was a trend toward higher cortisol production (P = 0.07) in RE animals. Higher total (P = 0.03), average (P = 0.07), and daily (P = 0.06) weight gains were observed for CA animals. RE steers produced a higher proportion of cells with minor sperm defects (P = 0.06). Greater vesicular glands development was observed in CA animals (P = 0.01). No effect of temperament was observed on sexual precocity, cryotolerance, or testosterone production. It was concluded that although temperament does not influence age at puberty, reactive bulls exhibit poorer performance in body development, vesicular glands development, and fresh semen quality compared to calm bulls.